Assessment of Flexible Shape Complementarity: New Opportunities to Explain and Induce Selectivity in Ligands of Protein Tyrosine Phosphatase 1B. Issue 5 (6th February 2019) - Naß, Alexandra; Schaller, David; Wolber, Gerhard
Abstract: For drug design projects it is essential to rationally induce and explain selectivity. In this context shape complementarity as well as protein and ligand flexibility represent important factors. Currently available tools for the analysis of protein‐ligand interactions focus mainly on electrostatic complementarity and/or static structures. Here we address the shortcomings of available methods by presenting two new tools: The first one can be used to assess steric complementarity in flexible protein‐ligand complexes in order to explain selectivity of known ligands. It further allows to determine ligand atoms with especially good or bad shape‐fit which can be of use in lead optimization projects. The second tool was designed to detect differences in protein flexibility in similar proteins along with their exploitation for virtual screening. Both tools yield interesting results when applied to data of protein tyrosine phosphatase 1B (PTP1B): The case of PTP1B has proven especially difficult in terms of selectivity, due to a closely related phosphatase connected to severe undesired effects. With our tool for steric complementarity assessment we were able to explain previously undisclosed causes of moderate selectivity of selected PTP1B ligands. The second tool allowed us to find differences of flexibility in the two highly similar proteins and give directions for exploitation in virtual screening. Abstract :